Longitudinal ECG changes in tetralogy of Fallot and association with surgical repair - Bhat, Misha; Malm, Torsten; Sjöberg, Gunnar; Nordenstam, Felicia; Hanséus, Katarina; Rosenkvist, Carl-Johan; Liuba, Petru (Frontiers in Cardiovascular Medicine, 2024)
Background: ECG abnormalities have been linked to adverse changes in right ventricular (RV) morphology and poor clinical outcomes in repaired Tetralogy of Fallot (rTOF). Our aim was to describe how ECG changes progress in early and intermediate follow-up and whether types of surgical strategy at the time of primary repair affected these changes. Methods: We studied patients with rTOF born 2000-2018 operated at our institution. Seven time points in relation to primary repair, follow-up, and pulmonary valve replacement (PVR) were identified. Patients correct with valve sparing repair (VSR), trans-annular patch (TAP) including with a monocusp valve (TAP+M) and with at least 3 ECGs were included. PQ interval, QRS duration, dispersion, and fragmentation, QTc duration and dispersion, JTc as well as presence of a right bundle branch block (RBBB) were analyzed. Medical records were reviewed for demographic and surgical data.Results: 219 patients with 882 ECGs were analyzed with a median follow-up time of 12.3 years (8.4:17) with 41 (19%) needing PVR during the study period. QRS duration increased at time of primary repair to discharge from 66 msec (IQR 12) to 129 msec (IQR 27) (p<0.0001) and at 1-and 6year follow-up but showed only a modest and temporary decrease after PVR. QTc increased at the time of primary repair as well as prior to PVR. PQ interval showed a small increase at the time of primary repair, was at its highest prior to PVR and decreased with PVR. Type of surgical repair affected mainly QTc and JTc and was consistently longer in the TAP+M group until PVR. In VSR, QTc and JTc were prolonged initially compared to TAP but were similar after 1 year. After PVR, there were no differences in adverse ECG changes between surgical groups.Conclusions: PQ interval and QRS duration best correspond to the assumed volume load whereas the relationship with QTc and JTc is more complex, suggesting that these represent more complex remodeling of the myocardium. Before PVR, QTc and JTc are longer in the TAP+M group which may be due to a longer surgical incision.